PHILOSOPHY OF MOTIVATION – SPIRITUAL FORCE THAT DRIVES TO HUMAN GOAL-ACHIEVEMENT - Sarvinoz Mukhamadieva (Modern American Journals, 2025)
This scientific article discusses the concept of motivation, its definition, classification, and its role in the spiritual life of society. On this basis, the subject, purpose, object, subject, and tasks of the philosophy of motivation are analyzed in a comparative manner, as well as the thoughts of Eastern and Western thinkers on this subject, and their role in shaping the philosophical thinking of young people is described.
Keywords: Motivation, internal motivation, external motivation, philosophy, philosophy of motivation, meaning, purpose, morality, identity, being, knowledge, value, spirituality, Human.